2020
DOI: 10.1186/s13052-020-00895-4
|View full text |Cite
|
Sign up to set email alerts
|

Pathological staging of chorioamnionitis contributes to complications in preterm infants

Abstract: Objective To investigate the effect of pathological staging of chorioamnionitis (CA) on complications in preterm infants; Methods A single-center, retrospective study was conducted to choose singleton preterm infants (gestational age < 37 weeks) from the Department of Obstetrics and Gynecology in our hospital from December 2016 to December 2017. The basic data and placental pathological results were retrospectively collected. According to the placental pathological results of whether inflammation infiltra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 46 publications
1
8
0
3
Order By: Relevance
“…Gestational Age (Mean ± SD) 28.09 ± 3.397 27.47 ± 3.893 0.55 Our study showed that mothers who had amnionitis were more likely to have a neonate with severe GMH-IVH. In consistent with our findings, previous studies showed that amnionitis could cause low GA and birth weight which they considered them as risk factors for severe GMH-IVH [8,9].…”
Section: Table 1 Analysis Of Gestational Age In Weeks Of Mild Gmh-ivh and Severe Gmh-ivh [T-test] Grade I And Ii Grade Iii And Iv P-valuesupporting
confidence: 93%
“…Gestational Age (Mean ± SD) 28.09 ± 3.397 27.47 ± 3.893 0.55 Our study showed that mothers who had amnionitis were more likely to have a neonate with severe GMH-IVH. In consistent with our findings, previous studies showed that amnionitis could cause low GA and birth weight which they considered them as risk factors for severe GMH-IVH [8,9].…”
Section: Table 1 Analysis Of Gestational Age In Weeks Of Mild Gmh-ivh and Severe Gmh-ivh [T-test] Grade I And Ii Grade Iii And Iv P-valuesupporting
confidence: 93%
“…Moreover, Apgar score, endotracheal intubation rate, mechanical ventilation rate, pulmonary surfactant application, severe PDA rate and the incidence of BPD in very low birth weight infants were related to HCA [18]. Maternal amnionitis led to the low gestational age and low birth weight of preterm infants, and it was an independent risk factor for intraventricular hemorrhage [19]. Therefore, it is extraordinarily urgent to discover possible risk factors and predictive biomarkers of intrauterine infection in the early stage to reduce the complications of preterm infants by intervening timely.…”
Section: Discussionmentioning
confidence: 99%
“…Внутрішньоутробна інфекція/запалення є причетним до розвитку ПВЛ, що надалі призводить до рухових і когнітивних порушень у немовляти, ДЦП, розладів аутичного спектра (РАС) та ін. [19].…”
Section: синдром системной воспалительной реакции плода (клиническая ...unclassified
“…• 1-а стадія -амніотропна міграція фетальних нейтрофільних гранулоцитів у стінку м'язового шару пуповинної вени (флебіт); • 2-а стадія -артеріїт; • 3-я стадія -некротичний фунікуліт з інфільтрацією желе Уортона (концентричне периваскулярне поширення дегенерованих нейтрофільних гранулоцитів) [19]. Виявлення тромбів також розглядають як серйозне запалення плода.…”
Section: синдром системной воспалительной реакции плода (клиническая ...unclassified
See 1 more Smart Citation